Integration of colorimetric and SERS detection for rapid screening and validation of melamine in milk1. Issue 15 (7th August 2015) - Lang, Tingting; Pang, Shintaro; He, Lili
<x xml:space="preserve">Abstract</x> Herein, we developed a novel method which integrated two gold nanoparticle (Au NP) based techniques, colorimetric and surface enhanced Raman spectroscopic (SERS) analyses, for rapid screening and validation of melamine in milk.